Adenoviral Pneumonia Outbreak in Immunocompetent Adults—A Missed Antimicrobial Stewardship Opportunity? - Branimir Gjurasin; Lorna Stemberger Maric; Tvrtko Jukic; Leona Radmanic Matotek; Snjezana Zidovec Lepej; Marko Kutlesa; Neven Papic (Antibiotics, 2025)
Background/Objectives: While the concept of viral community-acquired pneumonia (CAP) changed with COVID-19, the role of non-influenza viruses as a cause of CAP is less clear. The aim of this study was to describe the clinical course, risk factors, inflammatory profiles, antibiotic use, outcomes and complications of adenoviral (AdV) CAP. Methods: A prospective, non-interventional, observational cohort study included consecutively hospitalized immunocompetent adult patients with AdV CAP during an 18-month period. Clinical and laboratory data, including lymphocyte subpopulations and serum cytokine profiles were collected and correlated to clinical outcomes. Results: Fifty-eight patients with AdV CAP were included; 81% were males, with a median age of 33 (IQR 28–41) years and 62% without any comorbidities. All patients initially had high-grade fever for a median duration of 6 (5–7) days and respiratory symptoms. Increased CRP and procalcitonin, lymphopenia, mild thrombocytopenia and liver injury were frequent. Radiographic findings mimicked bacterial pneumonia (83% had unilateral involvement). Twenty-two patients (38%) had criteria for severe CAP, and these patients had higher procalcitonin, NLR, AST, ALT, LDH and CK, and lower T-lymphocyte CD4+ count. In comparison to influenza and bacterial CAP, patients with AdV had higher serum IL-2, IL-1β, IL-8, IL-10, CXCL10 and MCP-1, and lower TGF-β1 concentration. Thirteen patients required low-flow oxygen therapy, and 13 advanced respiratory support. Complications occurred in 29%, with one fatal outcome. While all patients received empirical antibiotic therapy, after AdV detection it was stopped in 21%, although only one patient had detected a possible bacterial coinfection. Conclusions: Since AdV CAP in immunocompetent patients is clinically and radiologically indistinguishable from bacterial CAP, it is associated with prolonged clinical course and lack of clinical response to antibiotics. This emphasizes the importance of AdV testing which could lead to more rational antimicrobial treatment.